DINAMIKA IDENTITAS ANAK MUDA DI ERA MEDIA SOSIAL: ANALISIS DENGAN TEORI HABITUS PIERRE BOURDIEU - Detia Adzra Athifah; Achmad Hufad (Prodi Sosiologi FISIP UPR, 2026)
Social media has now become the main place for young people in Indonesia to create and negotiate their identities. Interactions that take place in the digital world, algorithms from various platforms, and visual and performative cultures create new patterns of behavior that influence how teenagers see themselves and their roles in the digital community. This study explores this phenomenon through the lens of Pierre Bourdieu's habitus theory to explain how digital dispositions are formed from repeated experiences in using platforms such as TikTok, Instagram, and YouTube. This study applies a literature review method by analyzing various local and international studies. The findings show that young people's digital identities are not only influenced by personal decisions but also by social and digital structures such as algorithms, the aesthetics of each platform, and social, cultural, and symbolic capital. Young people also apply strategies of adaptation and rejection to the visibility rules set by platforms. This study emphasizes that identity in the social media era is a constantly changing process that is negotiated through interactions between youth agency and complex digital structures. These results provide deeper insights into how the identity of the younger generation is formed in today's digital society.